2005
DOI: 10.1111/j.1468-5884.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of relative distance in a driving simulator1,2

Abstract: The aim of this experiment was to test, in a driving simulator, how a subject can control his approach towards several simulated car-targets in different driving contexts. We assume that increasing complexity might influence driving performance according to the difficulty of perceiving distances properly. The subjects' first task consisted of placing their car at an equal distance between two preceding cars. In the second task, the subjects had to place their car level with the preceding car. The target cars w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…They found that simulator drivers tend to underestimate distances. Similar results were reported by Baumberger et al (35) and Farah et al (36). The latter also reported that the mean remaining headway to the opposing vehicle at the end of the passing maneuver in the simulator was approximately half that observed in the field, indicating that drivers are willing to accept higher risks in the simulator.…”
Section: Discussionsupporting
confidence: 85%
“…They found that simulator drivers tend to underestimate distances. Similar results were reported by Baumberger et al (35) and Farah et al (36). The latter also reported that the mean remaining headway to the opposing vehicle at the end of the passing maneuver in the simulator was approximately half that observed in the field, indicating that drivers are willing to accept higher risks in the simulator.…”
Section: Discussionsupporting
confidence: 85%
“…Our hypothesis was that participants would brake longer and harder when the brake scene was occluded, because they had to rely on the perceived compressed distance at the start of the brake (consistent with Gilinsky's model of distance perception). Baumberger, Flückiger, Paquette, Bergeron, and Delorme (2005) showed that drivers underestimated the distance by about 5 m when asked to position their car at mid-distance between two other cars that were moving in the adjacent right lane of the driver. Distance underestimation has been found in other virtual environments as well, for a variety of measurement methods such as verbal reporting of absolute distance, triangulation by pointing/walking, perceptually-directed action, and perceived size judgment (Knapp & Loomis, 2004;Loomis & Philbeck, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Generally, drivers tend to underestimate the distance to the car ahead of them (Baumberger, Flückiger, Paquette, Bergeron & Delorme, 2005), so they keep a longer distance than they would during manual driving. This finding seems to be less valid for driving while using CC, when they often kept short distances.…”
Section: Resultsmentioning
confidence: 99%